Taxonomic revision of Triplostegia (Caprifoliaceae: Dipsacales) - Niu, Yan-Ting; Barrett, Russell L.; Zhang, Zhu-Zhi; Lu, Li-Min; Chen, Zhi-Duan (Phytotaxa, 2019)
The genus Triplostegia is revised and only a single, geographically variable species, Triplostegia glandulifera, is recognised. Triplostegia grandiflora is formally included as a synonym of T. glandulifera. A revised description is presented encompassing the full range of observed morphological diversity following examination of 525 specimens. All names published in or referrable to Triplostegia are considered and discussed. Details of type specimens are enumerated to enhance the correct application of names. Three names were published independently in 1901, so the dates of publication must be carefully considered to establish priority if any taxa are segregated from T. glandulifera in future. A lectotype is designated for Triplostegia delavayi. Triplostegia aschersoniana is considered to be a valid combination based on Hoeckia aschersoniana.